Development of "Sam Contemporary Font" Typeface Based on Sam Poo Kong Temple Ornament - Dzuha Hening Yanuarsari; Agus Setiawan (Gelar : Jurnal Seni Budaya, 2022)
The ornamental design found in the architectural building of the Sam Poo Kong Temple gives an oriental unique characteristic. As a cultural heritage tourism destination, Sam Poo Kong Temple is required to develop the concept of information as part of good public service for visitors. Typeface design is a form of visual message design that can represent the image of the designed visual object. The purpose of this research is to design and develop an ornament-based typeface design from the Sam Po Kong Temple. The method used in this research is a descriptive-qualitative method with the ATUMICS theory approach for designing the typeface. In this context, the researcher wishes to bring back the decorative relief motifs that exist in the Sam Poo Kong Temple as a building element for new media with the mission of strengthening the image of the Sam Poo Kong Temple.